Occupational Characteristics Associated With Professional Fulfillment and Burnout Among US Physiatrists. (16th May 2023) - Makowski, Maryam S.; Trockel, Mickey; Paganoni, Sabrina; Weinstein, Stuart; Verduzco-Gutierrez, Monica; Kinney, Carolyn; Kennedy, David J.; Sliwa, James; Wang, Hanhan; Knowlton, Tiffany; Stautzenbach, Tom; Shanafelt, Tait D.
Abstract : Introduction: Multiple national studies suggest that among physicians, physiatrists are at increased risk for occupational burnout. Objective: The aim of the study is to identify characteristics of the work environment associated with professional fulfillment and burnout among US physiatrists. Design: Between May and December 2021, a mixed qualitative and quantitative approach was used to identify factors contributing to professional fulfillment and burnout in physiatrists. Setting: Online interviews, focus groups, and survey were conducted. Participants: The participants are physiatrists in the American Academy of Physical Medicine and Rehabilitation Membership Masterfile. Main Outcome Measures: Burnout and professional fulfillment were assessed using the Stanford Professional Fulfillment Index. Results: Individual interviews with 21 physiatrists were conducted to identify domains that contributed to professional fulfillment followed by focus groups for further definition. Based on themes identified, scales were identified or developed to evaluate: control over schedule (6 items, Cronbach α = 0.86); integration of physiatry into patient care (3 items, Cronbach α = 0.71); personal-organizational values alignment (3 items, Cronbach α = 0.90); meaningfulness of physiatrist clinical work (6 items, Cronbach α = 0.90); teamwork and collaboration (3 items, Cronbach α = 0.89). Of 5760 physiatrists contacted in the subsequent national survey, 882 (15.4%) returned surveys (median age, 52 yrs; 46.1% women). Overall, 42.6% (336 of 788) experienced burnout and 30.6% (244 of 798) had high levels of professional fulfillment. In multivariable analysis, each one-point improvement in control over schedule (odds ratio = 1.96; 95% confidence interval = 1.45–2.69), integration of physiatry into patient care (odds ratio = 1.77; 95% confidence interval = 1.32–2.38), personal-organizational values alignment (odds ratio = 1.92; 95% confidence interval = 1.48–2.52), meaningfulness of physiatrist clinical work (odds ratio = 2.79; 95% confidence interval = 1.71–4.71), and teamwork and collaboration score (odds ratio = 2.11; 95% confidence interval = 1.48–3.03) was independently associated with higher likelihood of professional fulfillment. Conclusions: Control over schedule, optimal integration of physiatry into clinical care, personal-organizational values alignment, teamwork, and meaningfulness of physiatrist clinical work are strong and independent drivers of occupational well-being in US physiatrists. Variation in these domains by practice setting and subspecialty suggests that tailored approaches are needed to promote professional fulfillment and reduce burnout among US physiatrists.